A neural network approach for predicting production volume of biofuels in Poland - Siuda, Krzysztof (Zastosowanie sieci neuronowych do prognozowania wielkości produkcji biopaliw w Polsce, 2021)
This article focuses on the creation of artificial neural networks (ANN) and their use in predicting the volume of biofuel production in Poland on the basis of historical data. Artificial neural networks are extremely useful in predicting events in which it is difficult to find determinism and cause-effect relationships. For this purpose 30 artificial neural networks of different topology were created. The analysed artificial neural networks had: one or two layers, from 4 to 8 neurons on the first layer and 4 or 6 neurons on the second layer. Moreover, the effect of delayed inputs and the effect of learning set size on prediction quality were analysed. The quality of each structure was evaluated based on the coefficient of determination, mean error, and mean square error. The stability of prediction was evaluated based on the sample standard deviation of RMSE and MAE. All the presented ANN structures were simulated five times and the best individual results included in the tables. The best results were obtained for an artificial neural network with two layers, four neurons in each layer and one delay. Overall, the second layer increased the stability of the prediction.
Ekonomia XXI Wieku = Economics of the 21st Century, 2021, Nr 24, s. 7-26
Keywords: artificial neural networks; biofuels; prediction; sztuczne sieci neuronowe; biopaliwa; predykcja